FRI0083 Elevated il-16 level is a non-genetic characteristic of patients with severe systemic lupus erythematosus. (1st June 2001) - Lard, LR; Roep, BO; Huizinga, TW
Abstract : Background: IL-16, origanilly named lymphocyte chemoattractant factor, is a cytokine which is mainly produced by CD8 + T cells. Several reports have described that increased levels of IL-16 are in part responsible for T cell abnormalities in SLE patients. Objectives: To investigate whether increased levels of IL-16 is a characteristic underlying susceptibility to SLE or is a characteristic of the disease itself. Methods: Accumulated organ damage was measured with the SLICC/ACR Damage Index. Twenty-five severe (SLICC/ACR: 4.9 + 2.5) and ten non-severe (SLICC/ACR: 1.0 + 0.8) SLE patients were included in this study. Also 11 first degree relatives and 12 healthy volunteers were included in this study. Plasma IL-16 levels were measured by ELISA. Results: No significant difference in the IL-16 levels of the first degree relatives of patients with SLE (38.3 + 11.1 pg/ml) were observed when compared to controls (31.2 + 10.1 pg/ml). In order to analyse characteristics of the SLE in relation to concentration of IL-16, IL-16 was measured in severe SLE patients (71.3 + 87.4 pg/ml; P = 0.025) compared to healthy controls. On the other hand, no significant differences were observed between the non-severe SLE patients (37.8 + 26.1 pg/ml) and controls. Conclusion: No evidence for increased IL-16 levels in first degree relatives of the SLE patients was observed. IL-16 is enhanced in SLE patients with a severe disease, but not in patients with non-severe disease, thereby suggesting that IL-16 is associated with disease severity, and not with susceptibility for SLE.